Looking inside the tunnelling barrier III: Spin polarisation in strong field ionisation from orbitals with high angular momentum - Kaushal, Jivesh; Smirnova, Olga (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
Strong field ionisation is known as optical tunnelling of an electron through the barrier created by the laser field and core potential. Time-dependent analytical R-matrix takes advantage of the semiclassical nature of electron dynamics in strong laser fields and naturally incorporates complex-valued trajectories in time propagation. The language of trajectories enables straightforward 'kinematic' interpretation of several new phenomena such as 'inversion' of the conventional propensity rules in photo-ionisation (Barth and Smirnova 2011 Phys. Rev. A 84 063415) and generation of spin-polarised electrons (Barth and Smirnova 2013 Phys. Rev. A 88 013401) during ionisation in strong laser fields. Both phenomena are due to the kinematics of the electron motion under the barrier and were predicted for short-range potentials, i.e. neglecting the electron-core interaction. However, the electron-core interaction can and does affect the kinematics of tunnelling defining the ionisation propensity rules (companion paper I) and spin-polarisation. The latter is the focus of this paper. We consider orbitals with arbitrary angular momentum and extend our results to positively charged ions.
CRIS-Team Scopus Importer:2023-04-20
Keywords: attoclock; electron spinpolarization; non-adiabatic Coulomb effects; strong field ionization